Peran teknologi dalam meningkatkan kualitas pendidikan di era digital - Zahro, Salsabila Raudhatuz (Maliki Interdisciplinary Journal, 2024)
In the digital era, technology has become an important component in various aspects of life, including education. However, in its application in the world of education, there are several challenges, such as infrastructure gaps, varied digital skills, and dependence on technology. This article analyzes the role of technology in improving the quality of education with a focus on the advancement of access, learning effectiveness, and student engagement.